Estudo e implementação de operações em ponto fixo em FPGA com VHDL 2008: aplicação em controle de sistemas em tempo discreto - Oliveira, Alisson Antônio de (2012)
There are machines that need large processing speed for its correct working, these machines have a critical time response processing. When it is considered that aspect coupled with the need for control of static and dynamic behavior of a system arrives at the controller with strong demands on runtime. This dissertation compares discrete controllers implemented in fixed point with different accuracies, using for both the simulation of the behavior of controllers manufactured in Matlab command language and VHDL 2008. VHDL 2008 still in development and standardization by the IEEE. The VHDL language is used in FPGAs that are high speed devices with parallel processing capability. The main objective of this work is the study and implementation of discrete controllers in FPGA with the help of the VHDL 2008 language, determining its strengths and limitations, particularly in regard to the structure of programming, error analysis and demand for resources. Results show that accuracy still need some improvements a standard to the VHDL 4.0, known as VHDL 2008, is delivered to the market a stable standard. However, knowing it limitations, it is possible implementations and use in conversion of analog signals to discrete, such as control and dynamic systems simulation like servomechanisms.